Analysis of spliceosome assembly and the structure of a regulated intron in Drosophila in vitro splicing extracts. - Spikes, D (1992)
We characterize spliceosome assembly in Drosophila embryonic nuclear extracts. Further, we show that these extracts contain high levels of a 5' to 3' exoribonuclease activity allowing rapid, convenient protection mapping of 5' splice site and branchpoint sequences. We use this assay to show, for the first time, that a regulated arthropod intron uses a remote branchpoint strikingly similar in structure to those observed previously in regulated vertebrate introns. These results provide new evidence that both regulated and constitutive splicing are similar in detail in vertebrates and arthropods indicating that the powerful genetic systems for analysis of splicing regulation in Drosophila are likely to be directly informative for regulated splicing throughout metazoa. In addition, we report formation of a novel class of intron-dependent complexes. Behavior of these complexes indicates that they represent a mutually exclusive, kinetically competing pathway with spliceosome assembly. We propose that this competition represents the basis for a kinetic proofreading mechanism enhancing fidelity of intron recognition. We also discuss possible implications of this model for regulated splicing.